2015
DOI: 10.1158/2326-6066.cir-15-0025-t
|View full text |Cite
|
Sign up to set email alerts
|

Tumoricidal Effects of Macrophage-Activating Immunotherapy in a Murine Model of Relapsed/Refractory Multiple Myeloma

Abstract: Myeloma remains a virtually incurable malignancy. The inevitable evolution of multi-drug resistant clones and widespread clonal heterogeneity limit the potential of traditional and novel therapies to eliminate minimal residual disease, a reliable harbinger of relapse. Here we show potent anti-myeloma activity of macrophage-activating immunotherapy (αCD40+CpG) that resulted in prolongation of progression-free and overall survival in an immunocompetent, preclinically validated, transplant-based model of multi-dr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Tpl2 negatively regulated Il-12p40 production in response to versikine ( Figure 1D), in a manner analogous to TLR agonists. 16 Whereas versikine induced Il-12p40 in isolation, concurrent Fcg receptor ligation through addition of ovalbumin (OVA)/anti-OVA immune complexes promoted Il-10 production and skewed macrophage polarization toward an immunoregulatory M2b phenotype (Il-12 lo -Il-10 hi ) 17 ( Figure 1E). Intact VCAN is thought to signal through TLR2.…”
Section: Resultsmentioning
confidence: 99%
“…Tpl2 negatively regulated Il-12p40 production in response to versikine ( Figure 1D), in a manner analogous to TLR agonists. 16 Whereas versikine induced Il-12p40 in isolation, concurrent Fcg receptor ligation through addition of ovalbumin (OVA)/anti-OVA immune complexes promoted Il-10 production and skewed macrophage polarization toward an immunoregulatory M2b phenotype (Il-12 lo -Il-10 hi ) 17 ( Figure 1E). Intact VCAN is thought to signal through TLR2.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent report from our group, 9 we showed that aCD40 agonistic immunotherapy reprograms innate immune cells to exert potent anti-myeloma activity ex vivo and in vivo. aCD40-induced anti-myeloma tumoricidal effects were largely independent of cytolytic NK, T or B cells, a finding that supports the active involvement of macrophages in this process.…”
Section: Cd40 Immunotherapy In Myeloma: Experience and Challengesmentioning
confidence: 91%
“…Therefore, TPL2 can be viewed as an "innate immune checkpoint" and rationally targeted in combination with aCD40-based immunotherapies. 9 The mechanism of action of strongly-agonistic aCD40 immunotherapy may be fundamentally different to that of weak-agonists or antagonists previously tested in myeloma with modest results (dacetuzumab, lucatumumab). 8 Whereas strong CD40 agonists may principally work through immunemediated mechanisms, weak-agonists/antagonists exert their effects primarily though antibody-dependent cell-mediated cytotoxicity (ADCC) and/or complement-mediated cytotoxicity (CMC).…”
Section: Cd40 Immunotherapy In Myeloma: Experience and Challengesmentioning
confidence: 99%
See 2 more Smart Citations